Evaluation of endothelialization of an occluder device with cardiac computed tomography and assessment of the pathological validation. - Ang Liu; Xuejing Duan; Ke Wang; Hongguang Fan; Li Li; Chaowu Yan (PLoS ONE)
Background Assessing the endothelialization of occlusive devices noninvasively remains a challenge. Cardiac computed tomography angiography (CTA) can be employed to evaluate device endothelialization based on contrast uptake within the occluder. Objective This study examined device endothelialization using cardiac CTA and investigated the pathological associations. Methods From January 2010 to May 2022, we retrospectively analyzed 25 patients (age: 50.00 [17.00, 52.00] years; 12 Female) who underwent surgical device removal within 1 month after cardiac CTA examination (implantation period: 29.00[0.50, 108.00] months). The contrast uptake within the occluder was determined using cardiac CTA. The relationship between contrast uptake within the occluder and the endothelialization status with pathology was analyzed. Results Contrast uptake within the occluder was identified in 76.00% of patients. Pathological examination confirmed incomplete coverage of fibrotic tissue and superposed neoendothelium on the surface of all devices exhibiting contrast uptake. This included no coverage in 47.37% of patients and partial coverage in the remaining cases. On the surface of all devices without contrast uptake, a complete range of fibrotic tissue was observed, with an incomplete range of superposed neoendothelium in 66.67% of patients. On the surface of devices with an implantation period > 6 months, 71.43% of patients had incomplete coverage of fibrotic tissue and superposed neoendothelium on the left disc, 42.86% of patients occurred the same on the right disc. Conclusions Contrast uptake within the occluder indicated incomplete endothelialization, as confirmed by pathological validation. Late endothelialization of the device occurs frequently, and further research is required to investigate related mechanisms.